Effect of Alloying Elements on the Sr Modification of Al-Si Cast Alloys - Elisa Fracchia; Federico Simone Gobber; Mario Rosso (Metals, 2021)
Strontium-based modifier alloys are commonly adopted to modify the eutectic silicon in aluminum-silicon casting alloys by changing the silicon shape from an acicular to a spherical form. Usually, the modifier alloy necessary to properly change the silicon shape depends on the silicon content, but the alloying elements’ content may have an influence. The AlSr10 master alloy’s modifying effect was studied on four Al-Si alloys through the characterization of microstructural and mechanical properties (micro-hardness and impact tests). The experimental results obtained on gravity cast samples highlighted the interdependence in the modification of silicon between the Si content and the alloying elements. After modification, a higher microstructural homogeneity characterized by a reduction of up to 22.8% in the size of intermetallics was observed, with a generalized reduction in secondary dendritic arm spacing. The presence of iron-based polygonal-shaped intermetallics negatively affects Sr modification; coarser silicon particles tend to grow close to α-Fe. The presence of casting defects such as bifilm reduces Sr modification’s beneficial effects, and little increase in absorbed impact energy is observed in this work.